2013
DOI: 10.1371/journal.pone.0068626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Butyrate and Its Synthetic Amide Derivative on Liver Inflammation and Glucose Tolerance in an Animal Model of Steatosis Induced by High Fat Diet

Abstract: Background & AimsNonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease. Insulin resistance (IR) appears to be critical in its pathogenesis. We evaluated the effects of sodium butyrate (butyrate) and its synthetic derivative N-(1-carbamoyl-2-phenyl-ethyl) butyramide (FBA) in a rat model of insulin resistance and steatosis induced by high-fat diet (HFD).MethodsAfter weaning, young male Sprague-Dawley rats were divided into 4 groups receiving different diets for 6 weeks: 1. con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
142
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 40 publications
18
142
2
1
Order By: Relevance
“…SCFAs such as acetate, propionate and butyrate, derive from fermentation of undigested and unabsorbed carbohydrates by microflora and they are utilized by the colonic mucosa, contributing to host health and gut microbiota composition [22][23][24]. Butyrate does not only represent a local source of energy for colonocytes, but it also plays a role in the regulation of systemic functions, such as inflammation and pain perception [3,17,19,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SCFAs such as acetate, propionate and butyrate, derive from fermentation of undigested and unabsorbed carbohydrates by microflora and they are utilized by the colonic mucosa, contributing to host health and gut microbiota composition [22][23][24]. Butyrate does not only represent a local source of energy for colonocytes, but it also plays a role in the regulation of systemic functions, such as inflammation and pain perception [3,17,19,25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite PPARs are mainly considered lipid sensors, regulating glucose and lipid metabolism in different tissues, their involvement in other physio-pathological conditions has been widely demonstrated [19,32,33]. Zapolska-Downar et al [28] reported a role for NF-kB and PPAR-␣ in the anti-inflammatory effects of butyrate in endothelial cells, as well as in colonocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as insulin resistance is associated with NAFLD, one could propose that butyrate may improve NAFLD. Indeed, Mattace Raso and coworkers showed that sodium butyrate protected high-fat fed rats from NAFLD (Mattace Raso et al, 2013). Altogether, these studies reveal a potentially important role of gut microbiota in the development of MetS, NAFLD and insulin resistance.…”
Section: Role Of Gut Microbiota In the Development Of Insulin Resistancementioning
confidence: 95%